Dietary Trivalent Chromium Exposure Up-Regulates Lipid Metabolism in Coral Trout: The Evidence From Transcriptome Analysis - Wei, Lu; Li, Yu; Ye, Hengzhen; Xiao, Juan; Hogstrand, Christer; Green, Iain; Guo, Zhiqiang; Han, Dong (Frontiers in Physiology, 2021)
Diet quality greatly affects an animal’s performance and metabolism. Despite the fact that trivalent chromium [Cr(III)] is considered an essential element and is widely used in nutritional supplements for animals and humans, the potential toxicity of Cr(III) is unclear. Here, liver transcriptome sequencing was performed on coral trout (Plectropomus leopardus) exposed to 200 mg kg–1 of dietary organic Cr(III) [as chromium picolinate (CrPic)] for 8 weeks. One-hundred-and thirteen differentially expressed genes (DEGs) were identified in response to Cr(III) stress, in comparison to the control, including 31 up-regulated and 82 down-regulated DEGs. Clusters of Orthologous Groups of proteins (COG) classifies DEGs into 15 functional categories, with the predominant category being related to lipid transport and metabolism (9.73%). The Kyoto Encyclopedia of Genes and Genomes (KEGG) assigned DEGs to six major categories with robust DEGs as part of the lipid metabolism pathway (18.58%). Moreover, KEGG functional enrichment analysis showed that these DEGs are primarily related to steroid biosynthesis, terpenoid backbone biosynthesis, and steroid hormone biosynthesis pathways, of which steroid biosynthesis was the most significant pathway, and 12 key up-regulated DEGs (dhcr7, dhcr24, ebp, lss, msmo1, sqle, cyp51, tm7sf2, sc5dl, fdft1, nsdhl, and hsd17b7) were found for steroid biosynthesis pathways. To validate the RNA sequencing data using quantitative real-time PCR (qRT-PCR), qRT-PCR results indicate that the expression of genes encoding HMGCR, TM7SF2, TRYP2, CTRL, EBP, LSS, and CYP51 were induced, while those encoding THRSP, LCE, and MCM5 were reduced, consistent with RNA-seq results. This findings provides the first evidence that a long-term high dose of Cr(III) intake causes lipid metabolism disorder and potential toxicity in fish. Cautious health risk assessment of dietary Cr(III) intake is therefore highly recommended for the commercial and/or natural diets of aquatic animals, which has previously largely been ignored.